Social integration of refugees is improving - Katja Schmidt; Jannes Jacobsen; Magdalena Krieger (DIW Weekly Report, 2020)
Five years ago, almost a million people came to Germany seeking refuge. Chancellor Angela Merkel responded to public concern over such a large influx of refugees with her well-known saying, "Wir schaffen das" (We can do this!). Much has happened since then. As this report shows, the German population's concerns over immigration have been decreasing since 2016. Nevertheless, refugees are increasingly concerned about xenophobia. At the same time, although their trust in key state institutions is high, they are less trusting of Germany's public administration system. One way of building mutual reliance might be to foster personal contact between refugees and local populations. However, the present study indicates that, so far, only around half of refugees have regular contact with Germans. Female refugees, in particular, have less contact with Germans. Government initiatives to create diverse social networks could be an important step toward greater integration.
Keywords: J15; J18; J19; F22; O15; R23; J14; 330; refugees; concerns about immigration; trust; integration; bridging ties